Analysis of Lycopene and Vitamin C Levels of Pomelo Citrus Fruit (Citrus maxima (Burm) Merr) Red n White Varieties From South Sulawesi - Masdiana Tahir; A. Trihadi Kusuma; Ekawati Ekawati (LPPM - Universitas Muhammadiyah Banjarmasin, 2018)
Pomelo citrus (Citrus maxima (Burm) Merr) is a fruit plant that has many chemical ingredients that are beneficial to health, including lycopene, flavonoids, provitamin A, vitamin C, pectin, carbohydrates, retinol, calcium and phosphorus. Lycopene is a bright red carotenoid pigment, which is found in red fruits as well as vitamin C. The purpose of this study was to determine of lycopene and vitamin C levels in pomelo citrus (Citrus maxima (Burm) Merr) red and white varieties from Pangkep Regency, South Sulawesi. The method using UV-Vis Spectrophotometry, at a wavelength of 471 nm for lycopene and 494 nm for vitamin C. The results showed that levels of lycopene pomelo citrus red variety was 32,444 mg/kg and white variety 2,801 mg/kg. Levels of Vitamin C in pomelo citrus red variety was 0,721 mg/g and white variety 0,107 mg /g. The content of lycopene and vitamin C of pomelo citrus red variety is greater than of white variety.